2021
DOI: 10.1097/inf.0000000000003395
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Plasma Metagenomic Next-generation Sequencing in a Large Pediatric Cohort

Abstract: Background: Plasma metagenomic next-generation sequencing (mNGS) has the potential to detect thousands of different organisms with a single test. There are limited data on the real-world impact of mNGS and even less guidance on the types of patients and clinical scenarios in which mNGS testing is beneficial. Methods: A retrospective review of patients who had mNGS testing as part of routine clinical care at Texas Children's Hospital from June 2018-August 2019 was performed. Medical records were reviewed for pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The earlier studys ( Geng et al., 2021 ; Yan et al., 2021 ) showed that low immunity was associated with multiple infections. Niles et al., ( Niles et al., 2022 ) in a retrospective study of 169 participants, showed that immune-related patients were more likely to obtain multiple microbial results from mNGS than patients with normal immune function.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier studys ( Geng et al., 2021 ; Yan et al., 2021 ) showed that low immunity was associated with multiple infections. Niles et al., ( Niles et al., 2022 ) in a retrospective study of 169 participants, showed that immune-related patients were more likely to obtain multiple microbial results from mNGS than patients with normal immune function.…”
Section: Discussionmentioning
confidence: 99%
“…Pertinent mcfDNA studies that include immunocompromised patients are summarized in Table 2. Overall, the clinical impact of Karius testing has varied widely across studies (range 7–80%) [7,41 ▪ ,42,43 ▪ ,44–47], which may be partly related to the absence of standardized impact definitions. Factors associated with positive clinical impact included immunocompromised status, infectious diseases/stewardship-led approval and support for interpreting results [49].…”
Section: Metagenomic Next-generation Sequencingmentioning
confidence: 99%
“…There have also been studies of cfNGS showing limited benefit. Niles et al ( 83 ) performed a retrospective review of 169 pediatric patients who underwent cfNGS and found that cfNGS had a negative clinical impact in 5.3% (9/169), a positive impact in 12.4% (21/169), and no impact in 82.2% (139/169) of patients. The authors concluded that cfNGS had some clinical impact on immunocompromised patients but had limited clinical impact when ordered for all patients.…”
Section: Benefitsmentioning
confidence: 99%
“…They concluded that with much more research, mNGS has the potential to become the next frontier of clinical microbiology and will likely be included in the clinicians' armamentarium for treating infectious diseases. Multiple other studies have addressed clinical impact, but all conclude that more research is needed to determine this definitively ( 5 , 30 , 50 , 82 , 83 , 96 , 97 , 98 ).…”
Section: Clinical Usementioning
confidence: 99%